Challenges and Barriers to Implementing Collaborative Governance for Linking Education and Industry - Masteri Farahani, Fateme (Management Strategies and Engineering Sciences, 2024)
The present study aims to identify the challenges and barriers to implementing collaborative governance in the linkage between education and industry to provide practical solutions for managers and stakeholders in this field. To achieve the research objectives, the theoretical literature, including the history, definitions, and theories related to collaborative governance, education-industry interaction, and existing barriers, was first reviewed. The study, based on an interpretive philosophical foundation and an inductive approach, employed a qualitative method and a grounded theory strategy. Participants were selected through purposive sampling and snowball techniques. Data were collected using interviews with 10 experts from academia, industry, and government sectors. The research data were analyzed using a three-phase coding process: open coding, axial coding, and selective coding. Based on data analysis, the barriers to implementing collaborative governance in the education-industry linkage were categorized into six dimensions: causal conditions, contextual conditions, intervening conditions, the core category, strategies, and outcomes. In causal conditions, factors such as a lack of financial resources and the absence of legal infrastructure were identified as key barriers. Contextual conditions included inappropriate organizational culture and traditional attitudes toward collaborative governance. Intervening conditions highlighted the impact of rapid technological changes and insufficient policy-making. The core category identified in this study was the inefficiency of governance structures, which serves as the central challenge in education-industry interaction. Proposed strategies included enhancing transparency, reforming regulations, and leveraging modern technologies to facilitate interactions. Positive outcomes of successfully implementing collaborative governance included increased innovation, strengthened collaborations, and improved educational effectiveness. The temporal scope of the study was 2024, and the spatial scope was higher education institutions and industries in Iran. The study results revealed that the barriers to implementing collaborative governance pertain to two levels: macro (policy-making and legislation) and micro (cultural development, planning, and operational tools). Accordingly, a combined top-down and bottom-up approach is recommended to address these barriers. This approach can foster effective interactions among academic, industrial, and governmental institutions, thereby enabling the successful implementation of collaborative governance.